2016
DOI: 10.1089/cell.2015.0087
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Induced Pluripotent Stem Cells from Diabetic Foot Ulcer Fibroblasts Using a Nonintegrative Sendai Virus

Abstract: Diabetic foot ulcers (DFUs) are nonhealing chronic wounds that are a serious complication of diabetes. Since induced pluripotent stem cells (iPSCs) may offer a potent source of autologous cells to heal these wounds, we studied if repair-deficient fibroblasts, derived from DFU patients and age-and site-matched control fibroblasts, could be reprogrammed to iPSCs. To establish this, we used Sendai virus to successfully reprogram six primary fibroblast cell lines derived from ulcerated skin of two DFU patients (DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…We characterized the cellular features of iPSC-derived fibroblasts by comparing them with age-and locationmatched fibroblasts of nondiabetic and diabetic origin from which they were initially reprogrammed. Primary fibroblasts were isolated from the foot skin of patients without diabetes [nondiabetic foot fibroblasts (NFFs)], foot skin of patients with type 2 diabetes [diabetic foot fibroblasts (DFFs)], and DFUFs from patients with type 2 diabetes (8,9,31) and were reprogrammed into iPSCs that met all criteria of pluripotency (32). Using a differentiation protocol that we previously developed ( Fig.…”
Section: Ipsc-derived Cells From Nondiabetic and Diabetic Patients DImentioning
confidence: 99%
See 1 more Smart Citation
“…We characterized the cellular features of iPSC-derived fibroblasts by comparing them with age-and locationmatched fibroblasts of nondiabetic and diabetic origin from which they were initially reprogrammed. Primary fibroblasts were isolated from the foot skin of patients without diabetes [nondiabetic foot fibroblasts (NFFs)], foot skin of patients with type 2 diabetes [diabetic foot fibroblasts (DFFs)], and DFUFs from patients with type 2 diabetes (8,9,31) and were reprogrammed into iPSCs that met all criteria of pluripotency (32). Using a differentiation protocol that we previously developed ( Fig.…”
Section: Ipsc-derived Cells From Nondiabetic and Diabetic Patients DImentioning
confidence: 99%
“…We have recently reported the generation of iPSCs from primary, DFU-derived fibroblasts (32). In the current study, we have characterized the cellular and 3D tissue phenotypes associated with iPSC-derived fibroblasts that were initially reprogrammed from DFUs, by comparing them to site-and age-matched fibroblasts from patients with diabetes but no ulcers and from nondiabetic patients.…”
mentioning
confidence: 99%
“…Remarkably, these newly induced fibroblasts from iPSCs from diabetic fibroblasts were similar to those from non-diabetic fibroblasts. 30 This provides evidence for the potential use of iPSCs to improve wound healing in diabetic patients. Indeed, a study by Khamaisi et al demonstrated that iPSCs in diabetic models exhibited more efficient wound healing and secreted higher levels of pro-angiogenic factors.…”
Section: Diabetic Woundsmentioning
confidence: 90%
“…Despite their great promise, the use of pluripotent stem cells whether induced or embryonic is limited by their tumorigenic potential [71][72][73]. Because iPSC and human embryonic cells are capable of differentiating into cells from any of the three germ layers, they also carry the potential to form teratomas in the undifferentiated state.…”
Section: Induced Pluripotent Stem Cells and Teratoma Formationmentioning
confidence: 99%